Mencegah Tindakan Bullying di Sekolah Dasar dengan Menguatkan Budaya Malu dan Bersalah pada Siswa - Purnomo, Aditya Rizqi Putra; Baeny, Fathur Rahman; Azizah, Endang Nur; Tussaddiyah, Halimah; Yatri, Ika; Nawawi, Azhar (Peneliti.net, 2023)
Bullying in school is a serious problem that causing negative impact on child. To prevent bullying, it is important to build up shame and culture on student. This culture help students developing empathy, responsibility and awareness for consequences of bad attitude. In this article, we are discussing about the important of shame culture and guilt culture also the strategy that can be applied to prevent bullying in elementary school. The strategy includes education of value and social morality, learning by example, developing positive and accurate consequences, parental involvement, social skill training, and building up anti-bullying commit. By applying these steps, schools are expected to create a safe, caring, and free from bullying environment.